Star Wars : Obi-Wan Kenobi - Houser, Jody (Marvel Worldwide, Inc., 2024)
Obi-Wan returns in the official adaptation of the hit series! When agents of the Empire pose a new threat, Obi-Wan Kenobi emerges after years of hiding. Years after the events of Revenge of the Sith, Obi-Wan is tasked with keeping both of the Skywalker children safe from a distance – until young Leia Organa finds herself held in a ransom plot! Can Obi-Wan save Princess Leia without the Empire realizing he’s alive? As he searches for allies, he must face his greatest failure: Darth Vader!